Buried Treasures and Ancient Forges: A Historical Analysis of Mines and Ironworks in the Stilaro Valley - Fiorenza, Elia (European Scientific Journal, ESJ, 2024)
This study aims to examine in detail the mines and ironworks in the Stilaro valley and the ancient ironworking process that took place there. Until the end of the 19th century, the area comprising the municipalities of Bivongi, Pazzano, Stilo, Fabrizia, Mongiana, and Guardavalle, represented one of the most significant iron and mining centers in southern Italy. This study is based on archaeological, historical, and archival sources to deepen the understanding of such economic and industrial activities that characterized the region. The historical and geological framework of the Stilaro valley provides an overview of the mineral riches and the complex mining and ironworking activities that have taken place over the centuries. Historical evidence, supported by significant findings, suggests an ancient presence of metalworking in the region, with an influence extending to Magna Graecia. The analysis of mines and ironworks reveals a complex dynamic of adaptation and interaction among ancient peoples, whose migration and settlement were influenced by the natural resources and economic opportunities offered by the region. The role of mines and ironworks not only contributed to local economic and industrial development but also shaped the cultural and social landscape of ancient and medieval Calabria. The implementation of conservation and enhancement projects, such as the Ecomuseum of the Ironworks and Foundries of Calabria, underscores the importance of preserving this historical and industrial heritage for future generations.